(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study examined the cardioprotective role of methanol extract of the edible mushroom Volvariella volvacea against oxidative stress in hyperglycemic rats. Rats divided into 6 groups were administered with nicotinamide and streptozotocin intraperitoneally, except Group I (control). Group II served as diabetic control. Group III was given glibenclamide. Two groups (IV and V) of rats received (200 and 400 mg/kg) mushroom extracts orally for 30 days and Group VI received vitamin E (40 mg/kg). After the treatment period, lipid peroxides, carbonyl end products, advanced glycation end products, reduced glutathione, glutathione peroxidase, glutathione-S transferase, catalase, superoxide dismutase and non-enzymatic anti-oxidants (vitamin C and E) were assessed in the heart tissues of experimental animals. Glycosylated hemoglobin was estimated in blood. Electrocardiography recordings of the treated groups were also done. The results showed that mushroom extract treatment reduced the lipid peroxides, advanced glycation end products and protein carbonyls significantly and reversed the altered anti-oxidant enzymes, and the vitamins. Video Clips of Methodology: Hemolysate preparation: 2 min 50 sec Full Screen Alternative Mixing, glycosylated hemoglobin separation and reading absorbance: 3 min 10 sec Full Screen Alternative